DNA genotyping of Kelampayang (Neolamarckia cadamba) progenies (sample set I) using Inter Simple Sequence repeat (ISSR) Marker - Valeria, S Kabalon (Universiti Malaysia Sarawak, (UNIMAS), 2012)
Neolamarckia cadamba, commonly known as Kdampayan is a fast-growing tropical timber species. It has many commercial applications such as production of plywood, pulp and paper, boxes and crates, furniture and light construction components. Currently, Kelampayan is a valuable species for the commercial forest plantation industry as it is able to help double the profits gained from timber industry. Molecular characterization of Ncadamba is needed so that the qualities of its progenies are maintained. In this project, DNA genotyping of Kelampayan were carried out to determine the genetic relatedness of Kelampayan progenies. One selected ISSR primers: (AGhC was used to assess the genetic diversity and genetic relatedness of ISO Ncadamba progenies (halfsib) from Matang OS, Lawas 24 and Lawas 29. This primer had successfully amplified 17 loci ranging between 389 bp to 1,047 bp, by which Lawas 29 was the most polymorphic (100% polymorphic). The Shannon's diversity index for Lawas 29 was the highest (0.44S3) compared to Matang OS (0.2064) and Lawas 24 (0.173 1) populations while the Gst value for the populations was 2.S837.The gene diversity within the population (Hs) was 0.1783, whereas the total gene diversity (H.) between the populations was 0.2128.